The influence of corporate governance and ownership concentration on the timeliness of financial reporting in Jordan - Aldaoud, Khaldoon Ahmad Mohammad (2015)
This study investigated the influence of corporate governance mechanisms and company attributes on the timeliness of financial reports among Jordanian listed firms. It also explored the moderating effect of ownership concentration on the relationship between internal corporate governance (board of directors and audit committee) and timeliness. Timeliness is measured using audit report lag (ARL), management report lag (MRL) and total report lag (TRL). This study covered 114 listed companies on the Amman Stock Exchange from 2009 to 2012 (N= 448). It was found that the firms, on average, took more than three months to release their financial reports. Hierarchical regression analysis was employed to examine if ownership concentration moderates the relationship between internal corporate governance and timeliness. The findings show that board independence, board diligence, audit committee presence, auditor’s opinion and institutional ownership are significantly related to ARL. Board size, CEO duality, audit committee presence, auditor’s opinion, auditor independence and institutional ownership are related to MRL. For the TRL model, the results also indicate that board independence, size, diligence, financial expertise and audit committee are related to total report lag. In addition, this study shows that company profitability, leverage and type of sector are related to timeliness. The results show that ownership concentration moderates the relationship between internal corporate governance and timeliness for all models (ARL, MRL and TRL). The findings indicate that a higher level of ownership concentration affect timeliness by confining the functions of the audit committees and the board of directors, and results in a delay in the financial reports. This means that a high ownership concentration which represents principal conflicts among the firms‘ managers hinders the firms' decisions to release their financial reports in a timely manner. This study concludes that good structures of corporate governance play a key role in improving the timeliness of financial reports.